Critical assessment of the production scale required for fossil parity of green electrolytic hydrogen. (10th July 2020) - Proost, Joris
Abstract: Hydrogen produced from renewable electricity through Power-to-Hydrogen can facilitate the integration of high levels of variable renewable electricity into the energy system. An electrolyser is a device that splits water into hydrogen and oxygen using electricity. When electricity is produced from renewable energy sources, electrolytic hydrogen can be considered to be green. At the same time, electrolysers can help integrate renewable electricity into power systems, as their electricity consumption can be adjusted to follow wind and solar power generation. Green hydrogen then also becomes a carrier for renewable electricity. Key green hydrogen production technologies, mostly PEM and alkaline electrolysers, are still further maturing, both in technical (efficiency), economical (CAPEX) and durability (lifetime) performance. Nonetheless, we will show in this contribution how fossil parity for green hydrogen, i.e. a Total Cost of Ownership (TCO) similar to grey H2 coming from todays CO2 intensive SMR processes, can already be achieved today. Moreover, this can be realised at a scale which corresponds to the basic units of renewable electricity generation, i.e. a few MW. Highlights: Electrolytic H2 is fossil-free when produced from renewable electricity. Today's price of H2 from fossil-based SMR processes (fossil parity) is 2, 0 €/kg. This can be reached for electrolytic H2 at a renewable electricity price of 30 €/MWh. The required electrolyser CAPEX of 500 €/kW can be reached already at a few MW. Such small-scale allows for decentralised H2 production in line with local H2 demand.